ANALISIS KINERJA BANK SYARIAH DENGAN METODE INDEKS MAQASID SYARIAH DI INDONESIA - ANDRIANI SYOFYAN (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. This study aimed to analyze the financial performance of Islamic banking in Indonesia using maqasid syariah index A behavioral approach operationalization method is used to quantify the Maqasid into measurable Islamic bank performance indicators that are later used for testing on a sample of four Islamic banks. The banks are evaluated and ranked at three levels based on their: 1) performance ratios, 2) performance indicators and 3) the overall Maqasid Index. This study used quantitative methods it is The Simple Additive Weighting or a weighted summation method. The results showed that the Bank Syariah Bukopin has the highst score in other words, Bank Syariah Bukopin showed better performance than the other three Islamic banks with maqasid syariah index.